Da Hegel a Nietzsche: la complessa relazione di Domenico Losurdo con il liberalismo - Shoikhedbrod, Igor (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
In this essay, I examine Domenico Losurdo’s treatment of Hegel, Marx, Engels, and Nietzsche with the aim of unearthing his critical entanglements with liber-alism. I will argue that Losurdo’s reflections on these thinkers betray a deeper ambivalence towards liberalism. This ambivalence ranges depending on which of the four thinkers is under Losurdo’s microscope. By closely engaging with Losurdo’s treatment of Hegel, Marx, Engels and Nietzsche, one leaves with a deeper grasp of these individual thinkers and the political implications of their respective philosophies. In much the same way, Losurdo’s work encourages readers to interrogate their own attitudes towards liberalism’s dialectic of eman-cipation and de-emancipation. The main difference about liberalism today is that it is under renewed attack from a variety of political quarters. Consequently, Losurdo’s critical entanglements with liberalism could not have come at a better time. Losurdo; Liberalism; Hegel; Marx; Engels; Nietzsche; Classical German Philosophy.